Effects of drying technique on the quality of Mola (Amblypharyngodon mola) dried by solar tent dryer and open sun rack dryer (Research in Agriculture Livestock and Fisheries, 2020)
Quality change of Mola (Amblypharyngodon mola) from open sun rack and solar tent dryer was evaluated at 1st, 2nd and 3rd days of drying. Sensory analysis showed that, solar tent dryer dry fish were excellent in overall quality of dry fish from open sun rack dryer. Moisture content of Mola from solar tent dryer was significantly (p>0.05) lower than the moisture content of dry fish from open sun rack dryer. Protein, lipid, ash and TVB-N content was significantly (p>0.05) higher in solar tent dried fish than dried fish from open sun rack. However, microbial load was higher on dry fish obtained from open sun rack dryer compared with the dry fish from low coat solar tent dryer. Moreover, the quality of the dried fish products from solar tent dryer was excellent in quality compared to the dried fish from open sun rack dryer.Res. Agric., Livest. Fish.7(1): 121-128, April 2020